A process-based approach to management of the enterprise; SHS Web of Conferences; Vol. 28 : Research Paradigms Transformation in Social Sciences (RPTSS 2015) - Ryzhakina T. G. Tatiana Gavrilovna (2016, 2016)
Title screen